Recent developments in epigenetics of pediatric asthma. Issue 6 (December 2016) - Harb, Hani; Alashkar Alhamwe, Bilal; Garn, Holger; Renz, Harald; Potaczek, Daniel P.
Abstract : Purpose of review: The goal of this review was to systematically analyze recent studies updating our knowledge on the role of epigenetic mechanisms in childhood asthma. Recent findings: A systematic literature search was conducted that identified 23 fresh articles published within the last 5 years reporting the results of human studies on the relationships between epigenetic modifications and childhood asthma or its/related phenotypes. In almost all these studies, meaningful associations between levels of epigenetic marks (DNA methylation and/or histone modifications) and pediatric asthma or its/related phenotypes have been observed. In addition, many studies identified by our screening analyzed those associations in the context of environmental factors, such as pollution, tobacco smoke, farming, or diet, showing in a huge majority a modifying effect of those exposures. Summary: The results of our systematic literature search provide a strong support for the role of epigenetic mechanisms in (mediating the effects of environmental exposure on) pediatric asthma. This knowledge may possibly be translated into diagnostic and/or therapeutic approaches.